The phage N4 virion RNA polymerase catalytic domain is related to single-subunit RNA polymerases - Kazmierczak, K.M. (Oxford University Press, 2002)
In vitro, bacteriophage N4 virion RNA polymerase (vRNAP) recognizes in vivo sites of transcription initiation on single-stranded templates. N4 vRNAP promoters are comprised of a hairpin structure and conserved sequences. Here, we show that vRNAP consists of a single 3500 amino acid polypeptide, and we define and characterize a transcriptionally active 1106 amino acid domain (mini-vRNAP). Biochemical and genetic characterization of this domain indicates that, despite its peculiar promoter specificity and lack of extensive sequence similarity to other DNA-dependent RNA polymerases, mini-vRNAP is related to the family of T7-like RNA polymerases.